Principal's managerial leadership in supporting teachers' tasks for strengthening the Pancasila student profile - Susanti, Erlin; Nur Sasongko, Rambat; Connie (Indonesian Journal of Educational Development (IJED), 2025)
This study evaluates the principal’s managerial role in optimizing teachers’ duties within the Pancasila Student Profile Reinforcement Project (P5) at State Senior High School 6 South Bengkulu using the CIPP evaluation model (Context, Input, Process, Product). The study is urgent as effective school leadership is essential to ensure P5 as a strategic program for character development in Indonesian education. Using a qualitative case study approach, purposive sampling was applied to select the principal, project coordinator, teachers, and students. Data were obtained through interviews, observations, and documentation, and analyzed thematically. Findings show that the principal’s role is aligned with school needs and national policies (context), facilitates module preparation and manages resources (input), establishes teams and supervises implementation (process), and enhances teacher performance, student engagement, and character development (product). Key challenges include limited funding, low student motivation, and difficulties in developing relevant project themes. The study recommends strengthening leadership and teacher capacity, improving financial and institutional support, and promoting adaptive policies to sustain P5 implementation.